2014
DOI: 10.1016/j.resuscitation.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of actual to estimated weights in Australian children attending a tertiary children's’ hospital, using the original and updated APLS, Luscombe and Owens, Best Guess formulae and the Broselow tape

Abstract: For an age-based weight estimation, in infants less than one year the new APLS formula is the most accurate and over one year the Best Guess formulae should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 16 publications
5
27
2
3
Order By: Relevance
“…In this study, the proportion of estimated weights that were within 10% of measured weights was approximately 75%. Other studies using the Broselow tape have reported proportions of estimated weights within 10% of actual weight of approximately 60%2 8 12 22 23 to 74%24 25 of measurements, and other existing formulas, such as the APLS and Luscombe formulas, result in accuracy proportions of 45%4 and 45%, respectively, in children 26. These findings indicate that our device outperformed other existing methods and devices in terms of accuracy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, the proportion of estimated weights that were within 10% of measured weights was approximately 75%. Other studies using the Broselow tape have reported proportions of estimated weights within 10% of actual weight of approximately 60%2 8 12 22 23 to 74%24 25 of measurements, and other existing formulas, such as the APLS and Luscombe formulas, result in accuracy proportions of 45%4 and 45%, respectively, in children 26. These findings indicate that our device outperformed other existing methods and devices in terms of accuracy.…”
Section: Discussionsupporting
confidence: 58%
“…There are some differences in anthropometric data according to race and nation. In multi-ethnic nations, the mean difference between the estimated weight and actual weight varies 8. In the present study, the mean difference for Asians/Indians was 3.91% compared with 11.6% among those of Maori descent.…”
Section: Discussioncontrasting
confidence: 52%
“…Since Broselow was derived using the Western population, they are more likely to overestimate weight when applied to a population of a developing country like India [8]. Recent studies have shown that Broselow is only accurate to only 48.9% [6]. Aside from having inconsistencies among varying ethnicities and body compositions, the Broselow Tape has its limitations, one of which would be when a patient exceeds the length of the tape.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Several studies have showed that this method tends to underestimate the actual weight and the margin of error increases with age. Another limitation of this method is that it uses different formula depending on the patient's age [5,6]. Since body habitus is not a factor, there may be an overestimation o underestimation of estimated weight of children who are underweight, overweight or obese [9].…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation